(untitled) (Biological Sciences - PJSIR, 2002)
Time course and dose dependent activity of elicitors (poly saccharides) obtained from Hypnea musciformis (red algae) was determined in terms of induced secondary metabolities in treated tissues of chickpea, followed by HPLC analysis. H. musc( formis of class Rhodophyceae (red algae) is widely distributed at the Karachi coast of Pakistan. Carrageenan are water extractable polysaccharides isolated from H. musciformis (Knutsen et al 1995). Generally these polysaccharides are ex tensively used as gels and thickening agents in food and industrial preparations (Bixler 1995). It is reported in literature that polysaccharides and oligosaccharides from plants, mi crobial cell wall and culture filtrate can regulate defensive and developing processes (Darvill and Albersheim 1984) and known as "Elicitors". Seaweeds are rich in polysaccharides, • we found worth exploring these polysaccharides as an elici tor of plant defense mechanism. Series of papers have been published for evaluating seaweed polysaccharides as an elici tor of disease resistance response in Chickpea tissues (Fatima and Seema 1999a and 2000). Antifungal properties of proteins (Agglutinins) isolated from H. musciformis are recently de scribed by Melo et al 1997.